High amniotic fluid fractalkine and MIP-1? levels are associated with intrauterine growth restriction: a prospective cohort study - Pala, Sehmus; Atilgan, Remzi; Ilhan, Nevin (Tubitak Scientific & Technological Research Council Turkey, 2024)
Background/aim: Proinflammatory chemokines have been shown to play crucial roles in implantation, spiral artery invasion, and the fetomaternal immunological response. In this context, we investigated the levels of fractalkine (CX3CL1) and chemokine CC motif ligand 4 (CCL4 or MIP-1 beta) in maternal serum and amniotic fluids in pregnant women with intrauterine growth restriction (IUGR). Materials and methods: This prospective cohort study was carried out at Firat University Obstetrics Clinic between January 1, 2022 and July 1, 2022. Group (G) 1: The control group consisted of 40 pregnant women who underwent elective cesarean section (CS) at 38-40 weeks of gestation. G2: A total of 40 pregnant women with IUGR at 28-37 weeks of gestation were included in the study group. Levels of tumor necrosis factor -alpha (TNF-alpha), interleukin-1 beta (IL-1 beta), interferon -gamma (IFN-gamma), hypoxia-inducible factor -1 alpha (HIF1 alpha), macrophage inflammatory protein -1 beta (MIP-1 beta), and fractalkine were measured in maternal serum and amniotic fluid samples obtained during CS. Results: When maternal age was compared, no statistically significant difference was observed between G1 and G2 (p = 0.374). The number of gravidity was found to be statistically higher in G1 compared to G2 (p = 0.003). The mean gestational week was statistically higher in G1 (p < 0.001). Maternal serum MIP-1 beta (p = 0.03) and IFN-gamma (p = 0.006) levels were higher in G1. The birth weight of the baby (p < 0.001) and umbilical cord blood gas pH value (p < 0.001) at birth were higher in G1. HIF-1 alpha (p < 0.001), fractalkine (p < 0.001), MIP-1 beta (p < 0.001), TNF-alpha (p = 0.007), IL-1 beta (p < 0.001), and IFN-gamma levels (p = 0.007) in amniotic fluid were higher in G2. Conclusion: Elevated levels of proinflammatory factors, including fractalkine and MIP-1 beta, along with inflammatory factors such as TNF-alpha, IL-1 beta, and IFN-gamma, as well as increased HIF-1 alpha levels in amniotic fluid, are associated with intrauterine growth restriction (IUGR) attributed to a hypoxic amniotic environment.
Keywords: IUGR; fractalkine; MIP-1 beta; HIF-1 alpha; amniotic fluid; inflammation